2018
DOI: 10.1155/2018/7425924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using a Blended Learning Method on Students’ Achievement and Motivation to Learn English in Jordan: A Pilot Case Study

Abstract: is research aims at investigating the effect of blended learning on the achievement and motivation to learn English of German Jordanian University students. A pilot case study research strategy was used. Pilot case studies are effective research strategies for investigating educational issues in real life situations. ey are used to refine research problems, variables, and also to refine the case study design before doing it in a larger-scale investigation. e study sample comprised 34 students who were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 6 publications
8
67
0
1
Order By: Relevance
“…It is also consistent with References [52,53] who Lack of plagiarism tools to monitor the character of student assignments. This result is logical with the work conducted by Reference [1] in which the researcher identified that plagiarism and credibility pose a major problem to blended learning; J 2019, 2, Firstpage-Lastpage; doi: www.mdpi.com/journal/j…”
Section: Respondents Identified the Following As The Strengths Of Blesupporting
confidence: 63%
See 4 more Smart Citations
“…It is also consistent with References [52,53] who Lack of plagiarism tools to monitor the character of student assignments. This result is logical with the work conducted by Reference [1] in which the researcher identified that plagiarism and credibility pose a major problem to blended learning; J 2019, 2, Firstpage-Lastpage; doi: www.mdpi.com/journal/j…”
Section: Respondents Identified the Following As The Strengths Of Blesupporting
confidence: 63%
“…It is further supported by References [5,20,[49][50][51][52] who observed that poor internet speed and connectivity is a heavy challenge in blended learning implementation;  Lack of plagiarism tools to monitor the character of student assignments. This result is logical with the work conducted by Reference [1] in which the researcher identified that plagiarism and credibility pose a major problem to blended learning;  There is a high risk of reduced face-to-face social interactions with blended learning mode. This outcome is consistent with the study conducted by Reference [53] where it was noted that in blended learning, learners may not only experience the isolation of lively social interaction with peers but also incapable to connect with their instructors;  The insufficient number of computers per student is also another challenge.…”
Section: Respondents Identified the Following As The Strengths Of Blementioning
confidence: 58%
See 3 more Smart Citations